Systematic Literature Review (SLR): Implementasi Pembelajaran menggunakan Pendekatan Understanding by Design (UBD) - Nina Nur Halimah; Laksmi Dewi (Institut Pendidikan Indonesia, 2023)
This study aims to identify and describe the Implementation of Learning using the Understanding by Design (UBD) Approach. This study aims to obtain a literature review on the effectiveness of Learning Design with the Understanding by Design (UbD) approach. The method used in this study is the Systematic Literature Review method. From the results of the strategy search, 70 articles were found from 2010 to 2022. Then they were gradually and systematically selected into 6 articles that were relevant to the topic of Learning. The results of this study indicate that there is an effect of the Implementation of Learning using the Understanding by Design (UBD) Approach. being more active during class, (2) Increasing the six aspects of understanding, explanation, interpretation, application, perspective, empathy, and self-knowledge, aspects of self-knowledge.